Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/cpt.359
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for the analysis of longitudinal electronic health records linked to claims data to study the effectiveness and safety of drugs

Abstract: Health insurance claims and electronic health records (EHR) databases have been considered the preferred data sources with which to study drug safety and effectiveness in routine care. Linking claims data to EHR allows researchers to leverage the complementary advantages of each data source to enhance study validity. We propose a framework to evaluate the need for supplementing claims data with EHR and vice versa to optimize outcome ascertainment, exposure assessment, and confounding adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 51 publications
2
40
0
Order By: Relevance
“…We found that in a real‐world setting, treatment with liraglutide 3.0 mg, in addition to recommended diet and exercise, was associated with a significant loss of 7.0 to 8.0 kg and with a 6.5% to 7.1% decrease in body weight 4 and 6 months post initiation. This study thus confirms that the effectiveness of liraglutide 3.0 mg, as an adjunct to diet and exercise, demonstrated in randomized clinical trials is also evident in a real‐world clinical setting, which may not always be evident given variability in the general population and in adherence to treatment .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We found that in a real‐world setting, treatment with liraglutide 3.0 mg, in addition to recommended diet and exercise, was associated with a significant loss of 7.0 to 8.0 kg and with a 6.5% to 7.1% decrease in body weight 4 and 6 months post initiation. This study thus confirms that the effectiveness of liraglutide 3.0 mg, as an adjunct to diet and exercise, demonstrated in randomized clinical trials is also evident in a real‐world clinical setting, which may not always be evident given variability in the general population and in adherence to treatment .…”
Section: Discussionsupporting
confidence: 78%
“…The clinical efficacy of liraglutide 3.0 mg has been established in randomized controlled clinical trials. Although these clinical trials offer a wealth of valuable information about safety and efficacy, the data derived from the highly controlled and specific population in the trials might not translate to a real‐world setting . Patients in the real world are subject to an uncontrolled environment and often experience a wider range of comorbidities and variable adherence to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…We used linked claims EHR data for higher data quality: The claims data provided comprehensive data across care settings, and EHRs provided necessary clinical information to ascertain TTR and important predictors. However, requiring overlap of the 2 databases reduces our sample size substantially and limits our ability to investigate each clinical outcome individually . Besides, for biophysiologic variables (eg, body mass index, albumin levels), we had 29% to 34% people with missing data in the relevant period.…”
Section: Discussionmentioning
confidence: 99%
“…However, requiring overlap of the 2 databases reduces our sample size substantially and limits our ability to investigate each clinical outcome individually. 55 Besides, for biophysiologic variables (eg, body mass index, albumin levels), we had 29% to 34% people with missing data in the relevant period. We handled it by the missing indicator method because not having certain tests done could, by itself, be informative of the general health state, and this approach allows use of these scores even if some variables are not available.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, treatments should be linked to clinical outcomes so that the best treatment can be selected. Increasingly, traditional sources of health-related data, such as claims databases, can be linked with clinical data from EHRs to better understand the safety of medications we prescribe to patients [8]. In fact, the wealth of information in all sources of data can be used to improve efficiency in clinical care [9] as well as compare the effectiveness of therapeutic options [10].…”
Section: Actors Of Reuse Research and Patient Carementioning
confidence: 99%